Dehydroepiandrosterone Sulfate Levels and Pulse Wave Velocity in Elderly Men - Takagi, Satoru; Isobe, Takeshi; Katoh, Nobuo; Fujiwara, Tadashi; Takeuchi, Hiroshi; Shimamoto, Kazuaki; Nakamura, Yosuke; Chiba, Yu; Saitoh, Shigeyuki (Japanese Journal of Cardiovascular Disease Prevention, 2005)
[Aim] To determine the relationship between dehydroepiandrosterone sulfate (DHEAS) levels and brachial-ankle pulse wave velocity (baPWV) in men. [Methods] The subjects were 114 men aged 59.1 ± 16.6 years, after exclusion of patients undergoing treatment for hypertension, diabetes and hyperlipidemia and patients with ABI of 0.9 or less, who participated in mass-screening tests in rural communities in Japan in 2003. After overnight fasting, body mass index, blood pressure in the sitting position (SBP / DBP), baPWV in the supine position, plasma glucose level, total cholesterol level, triglyceride level, HDL cholesterol level and plasma DHEAS level were measured. The subjects were divided into two age groups, 70 years of age or older (70 or older group) and less than 70 years of age (under 70 group). The subjects in each age groups were further divided into two DHEAS level groups, a high DHEAS (≥2148 ng/ml in subjects < 70 years of age and ≥1053 ng/ml in subjects ≥ 70 years of age) group (H-DHEAS subgroup) and a normal DHEAS (< 2148 ng/ml in subjects < 70 years of age and < 1053 ng/ml in subjects ≥70 years of age) group (N-DHEAS subgroup). [Results] The level of baPWV showed significantly positive correlations with age (r = 0.737, p < 0.001), SBP and DBP and a negative correlation with DHEAS (r =-0.481, p < 0.001). In the under 70 group, baPWV was significantly lower in the H-DHEAS subgroup than in the N-DHEAS subgroup (p = 0.015), though age was lower in the H-DHEAS subgroup than in the N-DHEAS subgroup. In the 70 or older group, baPWV was significantly lower in the H-DHEAS subgroup than in the N-DHEAS subgroup (p = 0.014) and there was no statistically significant difference between age in the H-DHEAS subgroup and that in the N-DHEAS subgroup. [Conclusions] DHEAS level is strongly influenced by aging. In this study, it was shown that baPWV increased as the level of DHEAS decreased and that a decrease in DHEAS level is one of the factors related to the progression of arteriosclerosis.